2020
DOI: 10.1007/s12639-020-01309-2
|View full text |Cite
|
Sign up to set email alerts
|

Animal hydatid cyst genotypes as a potential substitute for human hydatid cyst as a source of antigen for diagnosis of zoonotichydatidosis

Abstract: The Diagnosis of hydatidosis is still an unsolved issue due to difficulties in obtaining of patient's hydatid cyst appropriate for antigen extraction. This study evaluated the suitability of HC protoscolices somatic antigens (HCPsS-Ag) fractions from animal origin to substitute that extracted from HC of patients in diagnosis of hydatidosis using enzyme-linked immunoelectro-transfer blot and Enzyme-linked immunosorbent assay (ELISA). Eight fractions in HC-G6 from patients react specifically versus HC-G6 infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In addition, (Franssen et al, 2011) recorded a high number of muscles cysts, antibodies levels and immune response in rats experimentally infected with T. spiralis larvae as well as they reported that there was a positive correlation between the number of recovered muscles cysts of the infected rats and the level of serum antibody. However, there was no elevation in mean ELISA OD values in hosts slaughtered at 10 dpi and this is considered to be acceptable as (Bruschi et al, 2019;Ramadan et al, 2021) stated that the elevation in the level of anti-parasite Ab in sera could not be recorded before 2-3 weeks post-infection.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, (Franssen et al, 2011) recorded a high number of muscles cysts, antibodies levels and immune response in rats experimentally infected with T. spiralis larvae as well as they reported that there was a positive correlation between the number of recovered muscles cysts of the infected rats and the level of serum antibody. However, there was no elevation in mean ELISA OD values in hosts slaughtered at 10 dpi and this is considered to be acceptable as (Bruschi et al, 2019;Ramadan et al, 2021) stated that the elevation in the level of anti-parasite Ab in sera could not be recorded before 2-3 weeks post-infection.…”
Section: Discussionmentioning
confidence: 97%
“…Using SPSS 27 (IBM, NY, USA), The mean, maximum, and minimum values associated with every character, as well as the length/width ratios for the suckers and the body, were determined by a statistical description 26 , 27 .…”
Section: Methodsmentioning
confidence: 99%
“…The first part of this study used indirect ELISA to test the diagnostic specificity and sensitivity of these crude antigens in capturing anti-Cc-Ab in sera of surgically proven C. cerebralis infected sheep, control non-infected sheep, and sera collected from sheep infected by other parasites in order to identify the most diagnostic C. cerebralis antigen. CcF-Ag and CcS-Ag proved to have higher diagnostic sensitivity and specificity than CcW-Ag (Huang et al, 2016;Mahdy et al, 207;Ramadan et al, 2021). In contrast, CcS-Ag proved to have higher diagnostic specificity than the other two antigens.…”
Section: Efficacy Of Indirect Dot-elisa and Eitb For The Diagnosis Of...mentioning
confidence: 98%
“…ELISA specificity is usually affected by the degree of purity and specificity of the antigens (Sabry, 2007;Taher et al, 2017). EITB technique is considered a highly specific diagnostic technique, but it is unsuitable for field applications (Mahdy et al, 2017;Ramadan et al, 2021). The identification of specific diagnostic protein fractions then elution and concentration of this fraction to use in modified ELISA technique after dotting a minute amount of this purified antigen on NC sheet or even in micro-ELISA technique introduce more specific diagnostic assay described as dot-ELISA.…”
Section: Efficacy Of Indirect Dot-elisa and Eitb For The Diagnosis Of...mentioning
confidence: 99%
See 1 more Smart Citation